Bacterial load in public transport stopping fomites in the city of Portoviejo, Ecuador - Caicedo, Jennifer L.; Gómez, Wendy J.; Obando, Lesbia M. (Revista Gregoriana de Ciencias de la Salud, 2024)
The objective of this study was to evaluate the bacterial load on fomites at public transportation stops in the city of Portoviejo. Samples were collected from 12 public transportation stops by swabbing surfaces using Stuart transport medium. Subsequently, they were cultured on nutrient agar and MacConkey agar and incubated at 37 ºC for 72 h to perform microbial counts (CFU/cm2). Additionally, Gram staining tests were conducted to identify some samples of interest. The results showed significant variability between locations. Bus stops with higher public traffic exhibited higher levels of microbial load, while stops located in hospital activity areas did not show high levels of contamination. Several common bacterial genera were identified, including clusters of cocci and both Gram-positive and Gram-negative bacilli. The presence of potentially pathogenic bacteria underscores the importance of implementing effective infection control measures in these environments.